The Controversy of National Insight Test at KPK: A Sentiment Analysis on Twitter - Wiebi Winarto; Iradhad Taqwa Sihidia (Jurnal Ilmu Pemerintahan)
The issue of eradicating corruption in Indonesia is again in the public spotlight, this time related to the dismissal of 75 KPK employees because they were declared not to have passed the National Insight Test in order to transition to status as a State Civil Apparatus. Responding to issue, the community participated in expressing their views. However, the process of delivering opinions by the public isn’t done conventionally but through social media Twitter. This is a manifestation of the development of the digital democracy era, so the researcher intends to analyze the dynamics of twitter users in addressing the issue of the dismissal of 75 KPK employees, as a new way of democracy. The research uses a qualitative descriptive method, through a SNA approach by analyzing public sentiment on various people's 'tweets' on Twitter. The SNA data in question was obtained through the Drone Emprit database during the observation period from May 09 to May 12, 2021. The results obtained in the study showed that Netizens are divided into two groups, namely those who say they are pro against 75 KPK employees with a narrative of defending the dismissed KPK employees, while some other netters choose to oppose by bringing a narrative that the decision to dismiss is the right thing. Furthermore, it was concluded from the interactions of users of Twitter, the majority of netizens with various views expressed tended to support (Pro) 75 KPK employees who were dismissed. deliberately carried out by irresponsible with the mission of weakening the KPK.